Relationships between Components of Physical Activity and Heart Rate Variability in Older Women - Ligita Šilinė; Loreta Stasiulė; Arvydas Stasiulis; Renata Rutkauskaitė (Lithuanian Sports University, 2018)
Background. The level of daily activities of elderly persons decreases with aging. Also, reduced heart rate variability has been seen with normal aging. So, the aim of this study was to examine the relationships between physical activity and heart rate (HR) variability in older women. Methods. Nine healthy women were invited to participate in this study (age 67.0 ± 4.4). HR variability was assessed during active orthostatic test; physical activity was assessed by accelerometer. Results. Total physical activity was significantly correlated with mean HR (r = -.73), RRI (r = .73), RMSSD   (r = .83), HF (r = .78), SD1(r = .78) and SD1/SD2 (r = .72) in supine position. In addition total physical activity was significantly correlated with mean HR (r = -.68), RMSSD (r = .80), LF (r = .87), HF (r = .83), SD1(r = .82), SD2   (r = .65) and SD1/SD2 (r = .72) in standing position. Conclusion. Total physical activity is positively associated with higher heart rate variability in older women. Keywords:  physical activity, heart rate variability, older women.